Core‐Scale Experimental and Numerical Investigation on Fluoroboric Acidizing of a Sandstone Reservoir. Issue 7 (21st March 2016) - Zhou, Xiang; Zhang, Shicheng; Zhang, Xiong; Wang, Fei; Lin, Hun
Abstract: The acidizing of a sandstone matrix is an effective method to remove formation damage. Standard mud acid was the most commonly used fluid in the early days, however, the rapid decline in productivity after treatment promoted the development of numerous other fluid systems, and the fluoroboric acid system is one of the alternatives. In this work, experimental and numerical studies are conducted to investigate the performance of fluoroboric acid on sandstone. Firstly, the dissolution ability of fluoroboric acid and mud acid are tested at different temperatures. Then core flow tests are accomplished to further study the acidizing effect of fluoroboric acid and mud acid in porous media. Meanwhile, a core‐scale numerical model that considers the hydrolysis of fluoroboric acid and chemical reactions between HF and minerals is developed. The model was used to simulate core acid flooding by fluoroboric acid formulation and mud acid at different temperatures. Both the dissolution tests and core flow tests show that fluoroboric acid performs poorly at room temperature. However, if the temperature increases to 65 °C, the fluoroboric acid system has an equivalent dissolution ability to mud acid and the permeability enhancement by the fluoroboric acid system is 40 % higher than that of mud acid. The simulation results demonstrate that the trend of the core permeability change is consistent with the measured data. The model can provide the porosity and permeability distribution and the permeability profile along the flow direction, and this further explains the acidizing performance from a microscopic view. According to the simulation results, the permeability profile of the fluoroboric acid system is gentle at a higher temperature, which means moderate stimulation and deeper penetration. The simulation results demonstrate that mineral composition has a significant influence on the acidizing performance. With the same porosity, fast‐reacting minerals lead to a better acidizing performance. The model provides a reliable and effective method to optimize fluoroboric acidizing treatment. Abstract : Fluoroboric acidizing simulation : Formation damage is a common problem for sandstone reservoirs, which leads to a production decline. An improved 3 D model can simulate core acid flooding with fluoroboric acid and mud acid, obtain porosity and permeability distribution based on a heterogeneous model, and calculate the permeability profile along the flow direction, which provides a reliable and effective method to optimize the fluoroboric acidizing treatment.